2020
DOI: 10.30650/ajte.v2i1.268
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Edmodo in writing class: Why and how?

Abstract: ABSTRACT This paper comes up to discuss the theories and previous studies about using Edmodo in writing class. Using social network system in the Industrial era 4.0 helps teaching and learning activities become more effective because students can learn in and outside the class. Thus, it is helpful especially in writing class which require long learning time to use this kind of application. Therefore, utilizing an online applications in writing class can help students to improve their writing skill and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…These results match with the results reported in the study of Alka (2020). They reported that the usage of Edmodo in writing class has a positive impact on solving problems in writing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results match with the results reported in the study of Alka (2020). They reported that the usage of Edmodo in writing class has a positive impact on solving problems in writing.…”
Section: Discussionsupporting
confidence: 91%
“…The usage of Edmodo social learning networks for writing is thought to be more effective than traditional social networks (Asmara, 2021;Kurniawan & Surendro, 2018). This is supported by prior research, which has shown that Edmodo could be used effectively in writing classes (Mirza et al, 2022;Asmara, 2021;Alka, 2020;Paker & Doğan, 2019;Sofyan, 2017;Abadi & Merdad, 2015;Fauzi, 2015). that found that students who engaged in Edmodo-based learning had better writing results than those who did not utilize Edmodo.…”
Section: Flipped Learning Using (Sne)mentioning
confidence: 71%